Comparison of wet chemical treatment and Ar-ion sputtering for GaInP2(100) surface preparation. (15th August 2016) - Lebedev, Mikhail V.; Kalyuzhnyy, Nikolay A.; Mintairov, Sergey A.; Calvet, Wolfram; Kaiser, Bernhard; Jaegermann, Wolfram
Abstract: The interaction of the native oxide covered p-GaInP2 (100) surface with aqueous 1 M HCl and 40–48% (NH4 )2 S solutions is studied by high-resolution surface-sensitive photoemission spectroscopy excited by synchrotron radiation. The aqueous ammonium sulfide solution is more efficient in etching the native oxide layer than the aqueous HCl solution. After etching with any of the solutions, the gallium phosphates disappear completely and the surface remains covered with only a little amount of indium phosphates and hydroxides, gallium suboxides, as well as gallium and indium chlorides or sulfides, respectively. After wet etching a band bending of about 0.5 eV remains, as it is observed for the untreated surface. Ar ion sputtering of the native oxide covered p-GaInP2 (100) surface and subsequent annealing results in a strong increase of the Ga/In atomic ratio, in a decrease in the surface band bending, and in an increase in the surface work function. Since the Ar-ion sputtering and subsequent annealing results in considerable distortion of the near-surface layer of the p-GaInP2 compound, it cannot be considered as a satisfactory method for the preparation of a well-defined p-GaInP2 (100) surface. On the other hand, even after prolonged exposure (30 min) to aqueous HCl solution the chemical composition of the p-GaInP2 (100) surface etched with aqueous HCl solution remains stable, which can be of importance for the development of solar water splitting cells.